BPMN vs. UML Activity Diagram for Business Process Modeling - Cristina Venera Geambasu (Journal of Accounting and Management Information Systems (JAMIS), 2012)
During the last years, it has been noticed a growing interest of organizations in improving their business processes in order to be more competitive in a globalized economy that passes nowadays through a severe financial crisis with restrictive market conditions and limited profit margins. The first step in achieving this goal is to use an adequate business process modeling language to represent their business processes. For this purpose, an evaluation of the existing business process modeling languages would be very useful in making the right decision. Our research work comes to supplement the previous researches that have evaluated business process modeling languages. The evaluation performed in this paper is focused on the two most widely used graphical notations for business processes: Business Process Modeling and Notation (BPMN) and UML Activity Diagram (UML AD). The evaluation criteria are: capacity of being readily understandable, adequacy of the graphical elements of BPMN and UML AD to represent the real business processes of an organization and mapping to Business Process Execution Languages. The results of evaluating BPMN and UML AD against each of these three criteria are presented in the paper.
Keywords: M15; 650; Business Process Modeling; BPMN; UML Activity Diagram; Workflow Patterns; Business Process Execution Language